Is the library for “every body”? Examining fatphobia in library spaces through online library furniture catalogues - Chabot, Roger (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2021)
Despite Library and Information Science’s engagement with other matters of social justice, nearly no scholarly attention has been paid to fat issues within the library. Through the critical lens of the author’s own experiences as a fat Library and Information Science scholar, a critical discourse analysis of online library furniture catalogues reveals the exclusionary ways in which they perpetuate fatphobic body size standards. Given that library spaces are often considered a cornerstone of modern democratic societies, and that librarianship claims to champion ideals such as universal access to information, the exclusion of fat bodies in library spaces is problematic.